Evolution of spectral behavior and chemical composition in the tree canopy of a dehesa ecosystem - R. González-Cascón; J. Pacheco-Labrador; M. P. Martín (Revista de Teledetección)
In the context of the BIOSPEC and FLUXPEC projects (http://www.lineas.cchs.csic.es/fluxpec/), spectral and biophysical variables measurements at leaf level have been conducted in the tree canopy of a holm oak dehesa (Quercus ilex) ecosystem during four vegetative periods. Measurements of bi-conical reflectance factor of intact leaf (ASD Fieldspec 3® spectroradiometer), specific leaf mass (SLM), leaf water content (LWC), nutrient (N, P, K, Ca, Mg, Mn, Fe, and Zn) and chlorophyll concentration were performed. The spectral measurements have been related with the biophysical variables by stepwise and partial least squares regression analyses. These analyses allowed to identify the spectral bands and regions that best explain the evolution of the biophysical variables and to estimate the nutrient contents during the leaf maturation process. Statistically significant estimates of the majority of the variables studied were obtained. Wavelengths that had the highest contributions explaining the chemical composition of the forest canopy were located in spectral regions of the red edge, the green visible region, and the shortwave infrared.